NUMERICAL EVALUATION OF STRUCTURAL DYNAMICS AND HYDROELASTIC OF AN AUTONOMOUS UNDERWATER GLIDER - Revaldy Argapermana, Muhammad
This final project document contains a research report on the fluid-structure interaction (FSI) problem of an autonomous underwater glider (AUG). With a fuselage length of 2050 mm, fuselage diameter of 165 mm, wing span of 1365 mm, horizontal tail span of 344 mm, and speed range of 2.5 m/s - 5 m/s, the analysis is conducted on a composite sandwich wing structure with dimensions of 605.3 mm for the semi-span length, 150 mm for croot, and 100 mm for ctip. The research focuses on determining the dynamic characteristics and hydroelasticity instability of the AUG wing. Structural modeling to evaluate the dynamic characteristics of the wing structure, such as vibration mode shapes and natural frequencies, is performed using the finite element method (FEM) in the frequency range of 0-1000 Hz. Two structural models are used, one with CFRP skin and another with GFRP skin, both with a Polyurethane core. The Doublet Lattice Method (DLM), widely used for aeroelastic analysis of aircraft, is employed to evaluate unsteady hydrodynamic forces on the AUG wing. Subsequently, the hydrodynamic forces are combined with the FEM model to analyze hydroelasticity instability, including dynamic instability (flutter) and static instability (divergence). From the conducted dynamic characteristics analysis, it is found that the CFRP-skinned wing has a natural frequency twice as large as the GFRP-skinned wing. Furthermore, from the hydroelasticity instability analysis, it is found that both the CFRP and GFRP-skinned wing structures do not experience instability within the operational range (up to a maximum speed of 2.5 m/s). However, there is an indication of divergence for the CFRP-skinned wing at 5 m/s, and dynamic divergence is indicated for the GFRP-skinned wing at 6 m/s. It can be concluded that the AUG wing does not experience instability within its operational range.